(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: A number of specific clinical obstetric conditions can lead to coagulation failure with leading problems. One of the most common causes of significant coagulopathy is placental abruption. Placental abruption releases thromboplastin which can lead disseminated intravascular coagulation. D dimmers and FDPs are helpful in diagnosing these complications, D-dimers are the best indicators of disseminated intravascular coagulation. Objective: To assess the significance of D-dimers (epitope DD-3B6) as a diagnostic serological marker in patients of abruptio placentae Study Design: This community based, random, case control study was held from 2002 – 2004. Setting: The subjects were selected from the department of Gynecology and Obstetrics, Services Hospital, Sir Ganga Ram Hospital and Lady Willington Hospital, Lahore. Duration of Study: Study was carried between year 2002 -2004. Material and Method: Two groups were studied including a total of 60 subjects from 20 weeks of gestation onward. Twenty healthy pregnant females as controls and 40 pregnant pat -ients clinically diagnosed with Abruptio placentae were included in this study. Results: Among healthy control (group A) 25% (5) had D-dimer level less than 250 ng/ml while 75% (15) had levels above 250ng/ml. Among patients (group B) of abruptio placentae 5% (02) had D-dimers level less than 250 ng /ml while D-dimer levels above 250 ngs /ml were seen in 95% of patients. High D-dimer levels of more than 2000 ngs/ml were observed only in patients clinically diagnosed by the obstetrician with abruptio placentae 37.5% (15) as shown in Table -1. Conclusion: Plasma levels of D-dimer, were revealed to be reliable diagnostic markers of disseminated intravascular coagulation abruptio placetae. Using these markers, patients with poor outcomes, potentially life threatening condition, could be readily identified on admission